1973
DOI: 10.1039/dt9730000646
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of dicaesium octa-µ3-chloro-hexachloro-octahedro-hexa-tungstate(II) and -molybdate(II) complexes

Abstract: almost the same as the Mo-Mo distance (2-61-2-64 A) in (M06X8)4f.5-7 In contrast, the two-electron oxidation of the more weakly bound (Nb6X12)2+ increases the Nb-Nb distance from 2.92 to 3.016 and decreases the Nb-(axia1)Cl distance from 2-60 to 2.48 A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0
1

Year Published

1973
1973
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 0 publications
5
19
0
1
Order By: Relevance
“…As earlier reported in the publication of Healy et al [32], the systematic extinctions observed on the crystal data of Cs 2 Mo 6 Cl 14 allow structural refinements in two In the centrosymmetric space group P-31c, all crystallographic sites are fully occupied by the respective atoms except one of the two Cs cationic sites. Cs atoms are located on two Wyckoff positions: Cs1 on 4e (0, 0, z) with a 50% occupancy factor and Cs2 on 2c (1/3, 2/3, 1/4).…”
Section: Crystallographic Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…As earlier reported in the publication of Healy et al [32], the systematic extinctions observed on the crystal data of Cs 2 Mo 6 Cl 14 allow structural refinements in two In the centrosymmetric space group P-31c, all crystallographic sites are fully occupied by the respective atoms except one of the two Cs cationic sites. Cs atoms are located on two Wyckoff positions: Cs1 on 4e (0, 0, z) with a 50% occupancy factor and Cs2 on 2c (1/3, 2/3, 1/4).…”
Section: Crystallographic Resultssupporting
confidence: 60%
“…The synthesis of Cs 2 Mo 6 Cl 14 powder was performed according to a derivative method from that reported by Healy et al [32]. In a first step, (H 3 O) 2 Mo 6 Cl 14 Á7H 2 O was prepared as single crystals using the method reported by Koknat et al [30].…”
Section: Synthesismentioning
confidence: 99%
“…Durch Umsetzung von (n-Bu 4 N) 2[ (W 6 Cl i 8 )Cl a 6 ] mit CF 3 COOH in Dichlormethan wird zuna È chst ein Gemisch der Clusteranionen [(W 6 Cl i 8 )( CF 3 COO) a n Cl a 6Àn ] 2± , n = 1±6, hergestellt. In diesen lassen sich die in a È uûerer Spha È re koordinierten Trifluoracetatoliganden durch Behandlung mit NH 4 F leicht substituieren, und es bilden sich die Komponenten der Reihe [(W 6 Cl i 8 )F a n Cl a 6Àn ] 2± , n = 1±6, die durch die charakteristischen chemischen Verschiebungen der 19 Synthesis, Vibrational Spectra, and Crystal Structure of (n-Bu 4 N) 2 2± , n = 1±6…”
unclassified
“…By treatment with NH 4 F the outer sphere coordinated trifluoracetato ligands are easily substituted and the components of the series [(W 6 Cl i 8 )F a n Cl a 6Àn ], n = 1±6 are formed and characterized by their distinct 19 F NMR chemical shifts. An X-ray structure determination has been performed on a single crystal of (n-Bu 4 N) 2 C vib = 3 A 1g + 3 E g + 2 T 1g + 4 T 2g + A 2u + E u + 5 T 1u + 3 T 2u .…”
mentioning
confidence: 99%
“…2). The structure is that of the mixed cluster compounds Cs 2 [(M 6 Cl 8 )Br 6 ] (M = Mo, W) described in space group P31c [14], but it seems to us that the choice of the lower space group is artificial and without any proof of a solution with split positions with the cations. Cs1 is sixfold coordinated by Br a ligands at the corners of a strongly flattened octahedron with d(Cs±Br) = 3.603 A Ê .…”
Section: 3mentioning
confidence: 99%